A Critical Review of Civil Liability of Medical Science Researchers in Iran - Ali Arefi Maskouni (Kerman University of Medical Sciences, 2023)
Background: The importance of medical science development is well known to everyone, and conducting various studies is necessary to achieve this development. In the meantime, the occurrence of mistakes and failures in the process of conducting medical science research is inevitable. In such an atmosphere, the significance of the civil liability issue in medical science research becomes obvious, and since dealing with this area in private law has been neglected by the legislator, and this important matter needs particular laws, it requires legislation to recognize the legal foundations of that issue.Objectives: The current research was conducted aiming to critically review the civil liability issue of medical science researchers.Methods: The method used in this study was critical review. A review study helps us understand what we know at present in a specific scientific field.Results: Relying on each of the jurisprudential principles based on whether the study is therapeutic or non-therapeutic, and clinical or non-clinical, can lead to a different outcome in assigning liability to the researcher. Also, although there are definite foundations for civil liability in the legal system of Iran, in the field of medical science research, we are encountering a void of definite and revised regulations and procedures.Conclusion: In addition to recognizing the studies in medical sciences, it is also necessary to provide the possibility to induce the least legal challenges in therapeutic or non-therapeutic clinical studies on a human subject. Although there are civil liability foundations stemming from medical science research in Iranian law, unfortunately, no certain procedure and law are observed in this regard, and it is necessary for the legislator to resolve this serious void by approving appropriate regulations because due to the complexities in medical science subjects, the general principles of civil liability regulations cannot be a solution on its own.